2011
DOI: 10.1098/rsif.2010.0680
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured glass–ceramic coatings for orthopaedic applications

Abstract: Glass -ceramics have attracted much attention in the biomedical field, as they provide great possibilities to manipulate their properties by post-treatments, including strength, degradation rate and coefficient of thermal expansion. In this work, hardystonite (HT; Ca 2 ZnSi 2 O 7 ) and sphene (SP; CaTiSiO 5 ) glass -ceramic coatings with nanostructures were prepared by a plasma spray technique using conventional powders. The bonding strength and Vickers hardness for HT and SP coatings are higher than the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
5
28
0
1
Order By: Relevance
“…The surface modified technology was a good way to improve alloys' surface morphology, chemical composition and microstructure, which were thought to be important factors for implants' biological performance [10,11]. Calcium-phosphate ceramic are usually coated on the titanium alloys for its bioactivity on bone formation and bonding [12].…”
Section: Introductionmentioning
confidence: 99%
“…The surface modified technology was a good way to improve alloys' surface morphology, chemical composition and microstructure, which were thought to be important factors for implants' biological performance [10,11]. Calcium-phosphate ceramic are usually coated on the titanium alloys for its bioactivity on bone formation and bonding [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the rather passive properties of Ti, the osseointegration of Ti can be improved and the early effect of the implants remains unsatisfying [3][4][5]. Therefore, creating a bioactive surface for the TC is helpful to promote cell-material interactions and improve osseointegration of the implants [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these drawbacks, the design of the chemical composition and topography of the TiO 2 coating can be considered. Chemically, the biocompatible trace elements including Sr, Si and Zn have been utilized and their beneficial effects on the improvement of biological performance of implant have been proved [5][6][7]. Physically, it was reported that topography of implants can influence the cell behaviors including activation, adhesion, orientation, morphology and movement [8].…”
Section: Introductionmentioning
confidence: 99%